2019
DOI: 10.3390/jcm8050583
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intraoperative Inspired Oxygen Fraction on Postoperative Pulmonary Parameters in Patients with General Anesthesia: A Systemic Review and Meta-Analysis

Abstract: High intraoperative inspired oxygen concentration is applied to prevent desaturation during induction and recovery of anesthesia. However, high oxygen concentration may lead to postoperative pulmonary complications. The purpose of this study is to compare the postoperative pulmonary parameters according to intraoperative inspired oxygen fraction in patients undergoing general anesthesia. We identified all randomized controlled trials investigating postoperative differences in arterial gas exchange according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
(72 reference statements)
1
15
0
Order By: Relevance
“…The patients' Vt and RR during spontaneous breathing can meet the needs of intraoperative oxygenation, even in LMA anesthesia with 50% oxygen. Koo et al concluded that an oxygen concentration of 50% could decrease the risk of atelectasis caused by high oxygen concentration [19]. Our results showed that all patients maintained their SpO 2 at good level during the operation, including three patients whose preoperative SpO 2 was lower than 93%.…”
Section: Discussionsupporting
confidence: 54%
“…The patients' Vt and RR during spontaneous breathing can meet the needs of intraoperative oxygenation, even in LMA anesthesia with 50% oxygen. Koo et al concluded that an oxygen concentration of 50% could decrease the risk of atelectasis caused by high oxygen concentration [19]. Our results showed that all patients maintained their SpO 2 at good level during the operation, including three patients whose preoperative SpO 2 was lower than 93%.…”
Section: Discussionsupporting
confidence: 54%
“…High Fio 2 should be particularly directed to treatment or prevention of hypoxemia (e.g., preintubation and preextubation), and avoidance of Fio 2 of 1.0 might be most beneficial intraoperatively to patients at high risk for atelectasis. 212…”
Section: Inspired Fraction Of Oxygenmentioning
confidence: 99%
“…Koo CH concluded the oxygen concentration of 50% could decrease the risk of atelectasis which was caused by high oxygen concentration. 14 Our results showed that all patients kept their SpO 2 at 99.1±1.3%…”
Section: Resultsmentioning
confidence: 51%